A new species of Amanahyphes Salles & Molineri, 2006 (Ephemeroptera: Leptohyphidae) from Bahia, Brazil - Molineri, Carlos (2015)
A new species of the previously monotypic genus Amanahyphes Salles & Molineri, 2006 is described based on the male imago, egg and nymph from the state of Bahia, Brazil. Characters and illustrations to distinguish Amanahyphes bahiensis sp. nov. from A. saguassu and all other species in Leptohyphidae are provided. Amanahyphes bahiensis sp. nov. is diagnosed as follows: in the male imago, forewing shaded slightly with brownish at basal third and penes basally fused, distally with diverging lobes, and with a short spine-like projection at midlength on lateral margin; in the nymph, femoral spines long, slender and acuminate, tarsal claws with 10–11 marginal denticles and 2+3 subapical submarginal denticles, gill formula 3/2/2/2. Geographic records of both species are amended and indicated on a map.